Pengaruh Kualitas Pelayanan dan Promosi Terhadap Minat Peserta Didik di Madrasah Aliyah Unggulan Darul Ulum Jombang - Endar Ristiah (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Currently, competition in the world of education is increasing so rapidly that it cannot be avoided, both state and private educational institutions are competing to maintain their existence. The existence of educational institutions is characterized by high interest in new students. Efforts to attract new students by providing quality services and carrying out promotions. The research has independent variables, namely quality of service and promotion as well as the dependent variable interest in new students. This research method is quantitative with a causal associative approach. Respondents in this research were new students in class X of Madrasah Aliyah Unggulan Darul Ulum Jombang. The sampling technique used is Nonprobability Sampling. The data collection technique is by distributing questionnaires directly to respondents totaling 100 students. The results of this research show that service quality (X1) and promotion (X2) have a positive and significant effect on the interest of new students (Y) partially and simultaneously. The t test shows the coefficient value on the influence of X1 on Y, namely tcount > ttable (3.539>1.984), then the coefficient value on the influence of The F test has a coefficient value Fcount>Ftable (46.022>3.09).